Solution approach to civil service reforms challenges for effective service delivery in Nigeria - Mark, Ochala; Zainuddin, Ruslan (Society of Scientific Research and Education (SSRE), 2018)
The service delivery in Nigeria has remained a challenged while the erstwhile causes identified and solutions offered in the past have not really helped in the containment. Therefore, there is a need for a new approach to investigate the series of reforms that have been introduced by successive government. Centered on the research question set forth for this paper, sixteen informants who oversee the affairs of ministries and staff matters across different sphere of work force in Nigeria were probed about their perceptions on the possible solutions to the moribund reforms in civil service and service delivery in Nigeria. The sampling design was based on purposive method while Thematic data analysis technique was used to analyze the interviews data. However, qualitative computer data analysis software (NVIVO 10) was used to facilitate the process of storing, sorting, coding, analyzing and preparation of representation of the data. Arising from this, the paper established the nexus of solutions in relation to restructuring that requires creating enabling environment, carrying out employment by merit and federal character, introduction of comprehensive staff welfare and purging of corruption in the civil service. Similarly, as part of attempt to find answers to these challenges it was discovered that regular re-training of civil servants, improvement in the management of information and feedback to, the need for continuity of policy implementation and Prompt Response to public Complaints. Meanwhile, this study’s findings have significantly contributed to the understanding of the spiral of the challenges of the civil service reform through the solutions advanced by this study. These are imperative because identification of solutions could create efficient strategies for governments and lessons for civil servants.